Use of analytical lateral-axial strain relation in FE analysis of axially loaded rectangular CFST columns. (1st July 2018) - Ouyang, Y.; Kwan, A.K.H.
Highlights: Concrete in CFST has lateral expansion > predicted by plasticity theories. A lateral-axial strain relation is incorporated in FE model to resolve this problem. New FE model applied to analyse rectangular CFST specimens for verification. Used in a parametric study to evaluate ductility of rectangular CFST columns. Abstract: In a rectangular concrete-filled steel tube (CFST) column under axial compression, the concrete is under non-uniform and anisotropic confining stresses. To simulate such complicated triaxial stress field, finite element (FE) modelling is an effective tool. However, most previous FE models based on the plasticity theory augmented with associated or non-associated flow rules significantly underestimate the lateral and volumetric expansions of concrete at the inelastic stage and thus require solution dependent adjustments for compensation. Herein, an analytical lateral-axial strain relation of confined concrete derived from regression analysis of published experimental results is incorporated in a new FE model for the analysis of axial loaded rectangular CFST columns. This analytical lateral-axial strain relation allows direct evaluation of the lateral strains and should more accurately predict the lateral and volumetric expansions of confined concrete than the plasticity theory. The new FE model is applied to analyse tested specimens in the literature for verification and then used in a parametric study to evaluate the ductility of axially loaded rectangular CFST columns with different structural parameters.